IMPROVING STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT OF THE TENTH GRADE STUDENTS OF SMA NEGERI 11 PALEMBANG USING GIST - Yulia Anggraini; Yuyun Hendrety (Universitas Tridinanti Palembang, 2020)
This study aimed to find out whether or not there was any significant difference in students’ reading comprehension in narrative text between students who were taught by using GIST strategy and those who were not. Quasi experimental research was used in this study. The experimental group was taught by using GIST strategy meanwhile the control group was taught by using Discussion strategy. This study used purposive sampling. The samples of this study were 78 students of the tenth grade students of SMA Negeri 11 Palembang. Reading comprehension test was given as the technique for collecting data. To analyze the data, the researcher used paired and independent t-test. The finding of the study revealed that GIST strategy was more effective to help the students to understand the meaning of narrative text and improve their reading comprehension. There was also significant difference on reading comprehension between students who used GIST strategy and those who did not. It can be stated that GIST strategy can be an effective strategy to teach reading comprehension. It was also found that the students’ reading achievement of narrative text at the control group also improved significantly. However, the improvement achieved by the experimental group was higher than the control group.Keywords: reading comprehension, GIST, narrative text.